The Challenge of Recurrent Bacterial Vaginosis and The Promise of Liposomal Probiotic - Arnova Reswari; Delima Istio Prawiradhani Putri (Publikasi Indonesia, 2025)
Bacterial vaginosis (BV) is a common vaginal dysbiosis marked by the overgrowth of anaerobic bacteria and reduced Lactobacillus dominance. Despite antibiotic treatments, recurrence rates exceed 50% due to biofilm resistance and failed microbiota restoration. This narrative review describes that probiotics show promise but face challenges in colonization and stability. This review followed PRISMA guidelines, it screened 1,098 PubMed and Scopus studies (2015–2025). The studies used MeSH (Medical Subject Heading) terms like